Clostridioides difficile infection after surgical myocardial revascularisation: unravelling risk factors and impact on postoperative outcomes - Łuczak, Maciej; Greberski, Krzysztof; Burysz, Marian; Perek, Bartłomiej; Jarząbek, Radosław; Bugajski, Paweł (Journal of Medical Science, 2025)
Aim. Clostridioides difficile (CDI) poses a significant threat to postoperative cardiac surgery patients. This study examines the impact of specific pre-, intra-, and post-operative factors, along with geographical considerations, on Clostridioides difficile (CD) incidence and its consequences. The study aims to identify factors contributing to increased CD prevalence in cardiac surgery units. Material and methods. A single-centre cohort of 3502 patients undergoing surgical myocardial revascularisation between January 2013 and March 2018 was analysed, with 48 diagnosed with CDI. Preoperative risk factors include the use of broad-spectrum antibiotics, advanced age, comorbidities, and prolonged hospital stays. Intraoperatively, attention is given to catheter-related issues, mechanical ventilation, and the use of blood products. Postoperatively, the study assesses CDI’s impact on recovery, complications, and outcomes. A geographical analysis explores regional variation in CDI incidence. Results. Results indicate a CDI incidence of 1.37%, aligning with existing literature trends. Demographically matched controls show no significant differences in age, gender, or location. Higher Body Mass Index and lower left ventricular ejection fraction are identified as significant risk factors. Laboratory findings indicate elevated CRP levels and increased platelet count associated with CDI. Postoperative CDI significantly prolongs hospitalisation time. EuroSCORE II values are higher in the CDI group, though not statistically significant. Conclusions. The study offers a comprehensive understanding of CDI dynamics in cardiac surgery, emphasising the need for tailored preventive measures. Specific risk factors and regional variations underscore the importance of vigilant monitoring and early intervention. Future research should include larger cohorts and explore gut microbiota for refined strategies. In the later part of the abstract the authors use the abbreviation CDI. We suggest replacing this abbreviation with CDI.